Pembuatan Sensor Cahaya dengan Memanfaatkan LED dan LDR Berbasis Arduino Uno - Syukron, Ahmad Aftah; Isnaini Lilis Elviyanti (Jurnal Kridatama Sains dan Teknologi, 2021)
The recent technological developments are increasingly sophisticated and easy. So that the general public is easier to use. The development of this technology, then scientists are encouraged to create a new technologies. One that is often developed is the sensor. The aim of this research is to make a light sensor that utilizes LED and LDR as its main components. This light sensor can be used as alight measurement sensor from an optical material such as a fiber optic, or something else. The LDR performance testing as a detector is done by varying the light intensity of the hitting LDR. Test results show that the LDR sensitivity used is linear to the light intensity from the light source. Arduino uno is the main component of ADC. The ADC testing is done by varying the voltage on the arduino uno A0 analog pin from 0 V to 5 V in 0.1 V increments. In this research, the straight line equation y = 1.00532x + 0.00221 and R2 = 0.99988. From the this equation, it is known that the value of y is almost the same as the value of x and linearity is almost close to 1. This shows that the ADC output is almost the same as the input voltage. Keywords: Sensor, LED, LDR, Arduino Uno